Development of a comprehensive approach to determining the rational parameters of an onboard capacitive energy accumulator for a subway train - Sulym, Andriy; Fomin, Oleksij; Khozia, Pavlo; Palant, Oleksii; Stamatin, Vyacheslav (Eastern-European Journal of Enterprise Technologies, 2019)
One of the essential, yet insufficiently studied, issues related to the implementation of onboard capacitive energy accumulators in the subway is determining their rational parameters (power and energy intensity). We have analyzed existing methods and approaches to choosing the parameters for onboard capacitive energy accumulators. Disadvantages for each method and approach have been defined. We have substantiated the need to devise an approach that would make it possible to fully account for the factors influencing actual conditions of a subway train operation. Existing methods and approaches to selecting rational parameters have deficiencies and do not take into consideration the factors of real operating conditions of a subway train. This paper has proposed a comprehensive approach that takes into account the specified factors of influence and makes it possible to choose rational parameters for an onboard capacitive energy accumulator based on two indicators: the weight and cost of an accumulation system. We have determined the rational parameters for an onboard capacitive energy accumulator for the predefined operating conditions of a subway train using a comprehensive approach. The amount of saved electric power due to the implementation of an onboard accumulator with rational parameters has been calculated. The research results could be used when designing, constructing, and introducing the subway rolling stock with an onboard capacitive energy accumulator, as well as during an expert estimation of the amount of energy saved